Learning English Online from Home: The Challenges Faced by USIM BELCOM Students during MCO - Saiful Izwan Zainal; Noor Saazai Mat Saad; Norhana Abdullah; Suzanah Selamat; Ramiaida Darmi; Suraini Mohd Ali; Normazla Ahmad Mahir; Hazleena Baharun; Haliza Harun (USIM Press, 2024)
Efforts to curb the spread of the Covid-19 virus have been carried out on a large scale around the world, and among the measures that have been taken is to change the mode of learning among students in universities to online learning. Although various online learning platforms have been made available for student use, the level of mastery of students as well as the challenges they face to maximize the use of technology while studying from home is still understudied. This study will add to the previous research by focusing on the aspects of English language online learning processes experienced by Universiti Sains Islam Malaysia (USIM) students during the Movement Control Order period. This study collected qualitative data through open-ended questions which were distributed online, involving 29 first-year students from the Bachelor of English with Commerce (BELCOM). The data revealed two (2) categories of challenges – external and internal. Internet connection and environment are for external while understanding and communication are for internal. In relation to each of the challenges, the respondents also shared their coping mechanisms which are two-pronged. Some respondents just accepted those hurdles while many of them took charge and took action in solving the problems. These coping mechanisms could be used as guides for other learners facing difficulties in learning online at home.